Temporal trends analysis of emergency obstetric and newborn care availability and readiness index of healthcare facilities in Burkina Faso - Ilboudo, Dieudonné; Sombié, Issiaka; Koffi, Alain K.; Asiki, Gershim; Yaméogo, Téné Marcéline; Kirakoya-Samadoulougou, Fati (BMC health services research, 2024)
Background Ensuring healthcare services are equipped to offer; emergency obstetric and newborn care (EmONC) is crucial for improving the quality of maternal and newborn care in low- and middle-income countries. We assessed the temporal trends of the availability and readiness of the healthcare system to provide EmONC in Burkina Faso. Methods We analyzed the data from three national health facilities surveys, conducted in 2014, 2016 and 2018, using the WHO Service Availability and Readiness Assessment tool. We performed multivariable linear regression models to examine the trends. Results Between 2014 and 2018, the percentage of healthcare facilities providing delivery service and blood transfusion significantly decreased (88.1% to 75.4% for delivery services and 67.3% to 50.2% for blood transfusion, p < 0.001). The readiness index of healthcare facilities to provide basic EmONC showed a negative trend according to public healthcare, primary healthcare, and Centre-Nord, Centre-sud, Hauts-Bassins, Nord, Plateau Central and Sud-ouest health regions. Conclusions We observed multiple indications of a decline in the readiness of healthcare services to offer EmONC in Burkina Faso from 2014 to 2018. As such, bolstering the capabilities of health facilities to deliver EmONC is essential for hastening the decrease in maternal mortality.